2016
DOI: 10.1063/1.4944581
|View full text |Cite
|
Sign up to set email alerts
|

Enhancemet of flow boiling heat transfer in pHEMA/pPFDA coated microtubes with longitudinal variations in wettability

Abstract: Flow boiling heat transfer was investigated in stainless steel hypodermic microtubes, whose surfaces were enhanced by gradient crosslinked polyhydroxyethylmethacrylate (pHEMA)/polyperfluorodecylacrylate (pPFDA) coatings thereby offering variations in wettability along the surface as well as high porosity. The initiated chemical vapor deposition (iCVD) method was implemented for coating the inner walls of the microtubes with an inner diameter of 502 μm, and deionized water was used as the working fluid. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…At the highest mass flux the corresponding values were: 104%, 55%, and 19 %. Nedaei et al [72] extended the work by Kaya et al [71] and coated the 0.507 mm diameter tube such that the surface wettability (contact angle) can be different along the tube length, i.e. wettability gradient in the axial direction.…”
Section: Effect Of Surface Manufacturing Methodsmentioning
confidence: 98%
“…At the highest mass flux the corresponding values were: 104%, 55%, and 19 %. Nedaei et al [72] extended the work by Kaya et al [71] and coated the 0.507 mm diameter tube such that the surface wettability (contact angle) can be different along the tube length, i.e. wettability gradient in the axial direction.…”
Section: Effect Of Surface Manufacturing Methodsmentioning
confidence: 98%
“…However, a single homogeneous wetting surface cannot embrace the above conditions. The heterogeneous wetting surface can combine the advantages of strong wetting surface and weak wetting surface, which has excellent heat transfer performance for flow boiling (Nedaei et al 2016). Kousalya et al (2015) reported the horizontal subcooled flow boiling characteristics on the heterogeneous wetting surfaces (superhydrophilic -superhydrophobic) in a rectangular channel with a height of 5.5 mm, as shown in Fig.…”
Section: Construction Methods and Enhancement Flow Boiling Performance Of Heterogeneous Wetting Boiling Surfacementioning
confidence: 99%